(untitled) (Fiep Bulletin - online, 2011)
Larynx studies have contributed for the understanding of variations and diseases of this important organ. Recent publications and even the most traditional anatomy books don`t share the same opinion regarding the larinx cavities and that ultimately creates confusion and conflict. This study has as its main purpose to review the contemporary and acholar literature to redefine concepts and terminologies of the larynx cavity. It has been observed that the terminology and the contemporary definions have been going through changes and distorcinos alowly due to the lack of basis regarding the larynx cavities. Bringing back the old fashioned concepts such as supraglottic and glottic regions, the study have brought up great help to reorganize anatomical conceptual fundamental regarding the larynx cavities as definitions of glottis rima e glottis that are lagerly used in intensive care units in the clinical and surgical practices. Word-keys: larynx, revision, anatomy.